Pengaruh Profitabilitas, Ukuran Perusahaan Dan Umur Perusahaan Terhadap Audit Delay (Studi Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Tahun 2019-2021) - Shintike Indriyani Lahundo; Martinus Budiantara (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study investigates the audit delay phenomenon, where the process of examining financial statements by auditors is delayed in submitting audit results. Audit delay has the potential to be a serious concern in the business and financial context because it can interfere with the decision-making process and create uncertainty among investors, creditors, and other stakeholders. this phenomenon often occurs in various industrial sectors, thus driving researchers to examine the factors that have an impact on audit delay, including profitability, company size, and company age. This study focuses on property and real estate companies listed on the Indonesia Stock Exchange during 2019-2021. The multiple linear regression analysis method is used to identify the relationship between the independent and dependent variables. The research sample was selected through purposive sampling technique. The findings of this study confirm that profitability and company age can affect audit delay, while company size has no effect on audit delay. Keywords: Profitability, Company Size, Company Age, Audit delay